Review of the monograph by Maslikova Iryna "In search of the common good: ethical collision of social practices" (K.: Millennium, 2018. – 338 pp.) - O. V. Shynkarenko (Ukrainian Cultural Studies, 2019)
I. I. Maslikova's monograph is an important event in the domestic socio-humanitarian discourse. In it, for the first time, a comprehensive analysis of the phenomenon of the common good, which has been so little researched in the Ukrainian ethical space, especially in a systemic approach, is made.